Doubts and directions in translation studies : selected contributions from the EST Congress, Lisbon 2004 - Gambier, Yves, 1949-; Shlesinger, Miriam, 1947-2012; Stolze, Radegundis (Benjamins translation library ;, 2007)
Like previous collections based on congresses of the European Society of Translation Studies (EST), this volume presents the latest insights and findings in an ever-changing, ever-challenging domain. The twenty-six papers, carefully chosen from about 140 presented at the 4th EST Congress, offer a bird's eye view of the most pressing concerns and most exciting vistas in Translation Studies today. The editors' final choices reflect a focus on quality of approach, originality of topic, and clarity of presentation, and aim at capturing the most salient developments in the contemporary theory, meth.